Does government expenditure reduce inequalities in infant mortality rates in low- and middle-income countries? A time-series, ecological analysis of 48 countries from 1993-2013 - Baker,P; Hone,T; Reeves,A; Avendano,M; Millett,C (Health Economics, Policy and Law, 2018)
IntroductionInequalities in infant mortality rates (IMR) are rising in some Low and Middle-Income Countries (LMICs) and falling in others, but the explanation for these divergent trends is unclear. We investigate whether government expenditures and redistribution are associated with reductions in inequalities in IMR.MethodsWe estimated country-level fixed-effects panel regressions for 48 LMICs (142 country-observations). Slope and Relative Indices of Inequality in IMR (SII and RII) were calculated from Demographic and Health Surveys between 1993-2013. RII and SII were regressed on government expenditure (total, health, and non-health) and redistribution, controlling for GDP, private health expenditures, a democracy indicator, country fixed effects, and time.ResultsMean SII and RII was 39.12 and 0.69. In multivariate models, a one percentage-point increase in total government expenditure (% of GDP) was associated with a decrease in SII of -2.468 (95% CIs: -4.190, -0.746) and RII of -0.026 (95% CIs: -0.048, -0.004). Lower inequalities were associated with higher non-health government expenditure, but not higher government health expenditure. Associations with inequalities were nonsignificant for GDP, government redistribution, and private healthexpenditure.DiscussionUnderstanding how non-health government expenditure reduces inequalities in IMR, and why health expenditures may not, will accelerate progress towards the Sustainable Development Goals.